Efforts to Propagate the Sunnah in Nigeria; the Role of Majma’ al-Sunnah li al-Da’wah wa al-Buhuth (MSDB) in Ilorin - Adebayo, Baale Sheriff (Al-Bayān, 2022)
In an attempt to propagate the prophetic tradition, many organizations and study centres are established persistently. The propensity to practice pristine Islam and the Sunnah in Nigeria is generally suppressed with religious extremism and fanaticism campaign and political, economic, and social influence. Another dimension to this attitude towards Islam and Sunnah is the lack of knowledge and the zeal to learn. This research seeks to examine some of the efforts that MSDB has made to propagate the Prophetic Sunnah among the Nigerian Muslims Community. This research paper adopts the use of a thematic-narrative tool to analyse the personal interview had with the director of MSDB. The study developed a questionnaire instrument to measure the understanding of basic hadith concepts of past and present students, and those who attend some of the institution’s programs. A total of 211 samples were obtained and analysed using statistical methods. The study found that MSDB has given a significant rise in the Sunnah practices in Ilorin, Nigeria. The survey reveals that those who attend their programs understand the role of Hadith in expository comments of the Quran. The study also found a significant difference between individual knowledge of hadith and how frequently they attend MSDB programs. There is also a statistical significance between knowledge of hadith and the effect of MSDB in the community. However, there is an urgent need to replicate more Da’wah Centres, mosques, schools, and libraries that would encourage the practice and understanding of the prophetic tradition alongside that of the Quranic text in many communities in Nigeria as done by MSDB.